2021
DOI: 10.2967/jnumed.120.261651
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Parametric Imaging of 18F-FDG PET Using uEXPLORER with Reduced Scanning Time

Abstract: Parametric imaging of Ki (the net influx rate) in FDG PET has been shown to provide better quantification and improved specificity for cancer detection compared with SUV imaging. Current methods for generating parametric images usually requires a long dynamic scan time. With the recently developed uEXPLORER scanner, a dramatic increase of sensitivity has reduced the noise in dynamic imaging, making it more robust to employ a non-linear estimation method and flexible protocols. In this work, we explored 2 new p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 22 publications
(24 reference statements)
4
30
1
Order By: Relevance
“…Furthermore, we compared the quantification of DTW to several existing simplified quantification methods, including Patlak analysis, FUR, and SUV, as a surrogate for the net influx rate K i . The proposed DTW protocol produced the most accurate quantification, followed by FUR and Patlak analysis, while SUV had the lowest correlation, which is consistent with previous study findings [ 20 , 26 , 46 ]. In terms of visual performance, the DTW protocol generated parametric K i and K 1 images that were more consistent with the reference and had less noise than the Patlak analysis had.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, we compared the quantification of DTW to several existing simplified quantification methods, including Patlak analysis, FUR, and SUV, as a surrogate for the net influx rate K i . The proposed DTW protocol produced the most accurate quantification, followed by FUR and Patlak analysis, while SUV had the lowest correlation, which is consistent with previous study findings [ 20 , 26 , 46 ]. In terms of visual performance, the DTW protocol generated parametric K i and K 1 images that were more consistent with the reference and had less noise than the Patlak analysis had.…”
Section: Discussionsupporting
confidence: 91%
“…Many efforts have been made to avoid invasive blood sampling and shorten the duration of scans. Several noninvasive methods for determining the input function have been proposed, including image-derived input function (IDIF) [ 21 , 22 ], population-based input function (PBIF) [ 23 , 24 ], model-based input function [ 25 ], and hybrid input function [ 26 ] (combination of IDIF and PBIF). The difficulty in obtaining the input function for a bed position with no large artery in the field of view (FOV) is a concern when using these methods.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al. ( 29 ) explored and proved the possibility of shortened acquisition time for parametric imaging of K i in FDG PET scan employing the nonlinear estimation approach with 7 patients scanned on a total-body PET scanner. Wu et al.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar work, Wu et al showed that a dual imaging protocol that used PET data from 0 to 4 min and 54 to 60 min p.i can be used to estimate tumour K i with 12-30% bias [14]. In that same study, Wu et al also showed that a dual injection protocol can be used to estimate tumour K i with a 10 minute PET acquisition [14]. Use of PBIFs has also been evaluated with PET data acquired from SAFOV PET scanners.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work with LAFOV PET systems has shown that abbreviated dynamic imaging protocols can be used to extract net tissue in ux of 18 F-FDG, i.e. the Patlak slope, known as K i (ml g − 1 min − 1 ) with a total scan duration of 10 minutes [14]. We have also previously shown that K i and some of the kinetic microparameters can be estimated with low bias and good precision with a total scan duration of 15-20 minutes [15].…”
Section: Introductionmentioning
confidence: 99%